Mixed-mechanism analgesics for mixed pain - Raffa, Robert B. (Frontiers in Medicine, 2025)
The concept of “mixed pain” simultaneously highlights the benefit of integration of emerging advances in basic science (in particular, physiologic mechanisms) with advances in clinical care (symptomatology and diagnosis), and highlights some current prevailing challenges for both. This dichotomy is reflected in the very definitions or descriptions of mixed pain as a type of pain that manifests with symptoms that include those indicative of both nociceptive pain (viz., pain arising from tissue damage) and of neuropathic pain (i.e., pain arising from nerve damage), and possibly including other types of pain. The dichotomy also underscores the difficulty that is encountered treating such condition(s). Pharmacologic approaches are often accompanied by a variety of complementary non-pharmacologic approaches such as physical therapy, cognitive-behavioral therapy, immune and nutritional boosters, and a host of other modalities aimed at the attenuation of pain. This Perspective reviews the centrally-acting analgesics that have mixed mechanisms of analgesic action.